Distribution of subjective health complaints, and their association with register based sickness absence in the Danish working population. Issue 2 (March 2013) - Poulsen, Otto Melchior; Persson, Roger; Kristiansen, Jesper; Andersen, Lars Louis; Villadsen, Ebbe; Ørbæk, Palle
Aims : To describe the distribution of subjective health complaints (SHCs) in a Danish working population and the associations between SHC and register based sickness absence. Methods : The study entailed 2876 men and 3574 women aged 18–59 years that constituted the 2005 panel in the Danish Work Environment Cohort Study (DWECS). All had completed a subjective health complaints inventory and the Nordic Musculoskeletal Questionnaire (NMQ). Seven SHC/NMQ indices were constructed and merged with subsequently collected data on prolonged sickness absence periods (each period > 14 days) that was registered in the national Danish register on social transfer payments: the DREAM register. Ordinal logistic regression was used to model the cumulative odds for sickness absence as a function of strata. Results : The majority of participants reported at least one SHC during a 30-day period (circa 89% of the men and 95% of the women). The reports of severe SHC, defined as recurring SHC within the 30-day period, were less common. About 55% of the men and 68% of the women reported at least one severe SHC during a 30-day period. The odds ratios of sickness absence increased with the number of SHC a participant acknowledged. The odds ratios were slightly reduced after adjusting for age, disease history and social class. Conclusions : The majority of the working population in Denmark report at least one SHC during a 30-day period. Roughly half of the population report having at least one recurrent (often to very often) SHC during the last 30-days (severe SHC). Reporting the presence of several SHCs increases the likelihood of having more prospectively registered periods of sickness absence above two weeks.